2016
DOI: 10.3389/fpsyg.2016.00151
|View full text |Cite
|
Sign up to set email alerts
|

When “He” Can Also Be “She”: An ERP Study of Reflexive Pronoun Resolution in Written Mandarin Chinese

Abstract: The gender information in written Chinese third person pronouns is not symmetrically encoded: the character for “he” (, with semantic radical , meaning human) is used as a default referring to every individual, while the character for “she” (, with semantic radical , meaning woman) indicates females only. This critical feature could result in different patterns of processing of gender information in text, but this is an issue that has seldom been addressed in psycholinguistics. In Chinese, the written forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
(115 reference statements)
3
13
0
Order By: Relevance
“…Osterhout and colleagues (1997) reported qualitatively similar ERP effects for pronouns mismatching with either gender definition (mother, father) or the gender stereotype (nurse, doctor) of the previous antecedent. They reported increased positive amplitude shifts starting after 600 ms in the posterior scalp regions that they identified as P600s (similar results in Canal et al, 2015;Su et al, 2016). While some authors claimed that the P600 reflects syntactic processing (e.g., Kim & Osterhout, 2005), recent views suggest that it can reflect more general language integration (e.g., Brouwer et al, 2012), repair and reanalysis (e.g., Friederici, 2011) or more general conflict monitoring (e.g., van de Meerendonk et al, 2010; for a review Kuperberg, 2007).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Osterhout and colleagues (1997) reported qualitatively similar ERP effects for pronouns mismatching with either gender definition (mother, father) or the gender stereotype (nurse, doctor) of the previous antecedent. They reported increased positive amplitude shifts starting after 600 ms in the posterior scalp regions that they identified as P600s (similar results in Canal et al, 2015;Su et al, 2016). While some authors claimed that the P600 reflects syntactic processing (e.g., Kim & Osterhout, 2005), recent views suggest that it can reflect more general language integration (e.g., Brouwer et al, 2012), repair and reanalysis (e.g., Friederici, 2011) or more general conflict monitoring (e.g., van de Meerendonk et al, 2010; for a review Kuperberg, 2007).…”
Section: Introductionsupporting
confidence: 63%
“…Future research should address this issue. However, it is worth mentioning that previous studies on gender stereotypes (in which role nouns abounded) consistently reported P600 effects (Canal et al, 2015;Osterhout et al, 1997;Su et al, 2016) and no N400s. The present study differs from previous research by focusing on a full factorial design, on a different syntactic construction and on a morphology-rich language like Spanish.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…One widely used syntactic strategy is to argue that apparent long-distance binding effects can be derived from local dependencies. For example, Tang ( 1989 ) (see also Cole et al, 1990 ; Cole and Sung, 1994 ; Cole and Wang, 1996 , etc.) analyzed long-distance binding as involving a series of movements at the level of logical form such that each movement satisfies the requirement of local binding.…”
Section: Introductionmentioning
confidence: 99%
“…Native speakers' judgments vary regarding the ability of intervening third person referents to block long-distance binding. For example, Tang ( 1989 ) and Pollard and Xue ( 1998 ) treat blocking as a symmetric process whereby a difference in person feature between a local referent and a long-distance referent suffices to induce blocking (regardless of the person feature of the intervening referent). Based on this view, the matrix subject wo (“I”) in (3) cannot antecede the reflexive ziji , even though the intervening referent is third person.…”
Section: Introductionmentioning
confidence: 99%